Systemic in vivo delivery of siRNA to tumours using combination of polyethyleneimine and transferrin–polyethyleneimine conjugates - Grabowska, Anna M.; Kircheis, Ralf; Kumari, Rajendra; Clarke, Philip; McKenzie, Andrew; Hughes, Jaime; Mayne, Cerys; Desai, Arpan; Sasso, Luana; Watson, Susan A.; Alexander, Cameron (Royal Society of Chemistry, 2015)
Materials for delivery of oligonucleotides need to be simple to produce yet effective in vivo to be considered for clinical applications. Formulations of biomaterials based on combinations of existing demonstrated polymeric gene carriers with targeted derivatives are potential candidates for rapid translation but have not been fully explored for siRNA applications. Here we investigated formulations based on derivatised PEI for delivery of siRNA to gastrointestinal cancer cells. siRNA was complexed with linear PEI alone or with a mixture of linear PEI and transferrin-conjugated branched PEI (TfPEI), and knockdown of reporter genes was investigated. Overall, the in vitro use of complexes containing TfPEI resulted in up to 93% knockdown at 72 h post-transfection. Sustained knockdown was also achieved in a bioluminescent xenograft model. When complexes were delivered intratumorally, a 43% reduction in luminescence was achieved in the treated group compared with the control group 48 h after treatment. For systemic administration, only the intraperitoneal route, and not the intravenous route was effective, with 49% knockdown achieved at 72 h and sustained up to 144 h (44%) after a single administration of TfPEI-complexed siRNA. No toxicity or induction of the interferon response was observed. These findings demonstrate that simple formulations of transferrin-conjugated PEI with a ‘parent’ polymer such as linear PEI have potential as a method for therapeutic delivery of siRNA when administered either intratumorally or systemically.